Determinants of Real Exchange Rate: A Behavioural and Fundamental Dynamic Analysis in Latin American Countries - Chavez, Cesar (Universitas Airlangga, 2020)
In this research, we analyze the determinants of the real exchange rate through the fundamentals and behavioral factors, adding other variables as monetary aggregates, economic growth, domestic savings, and productivity. We worked with thirteen Latin American countries from 1980 to 2018 and we used three estimates such as fixed-effects, random-effects, and System GMM. The findings show that although the real exchange rate has a large random component, due to the high coefficient presented by the past values of that variable, there are other variables such as terms of trade, net foreign assets, tax revenue, monetary aggregates, savings rates and productivity, or real interest rate differentials, relative price and economic growth, which can impact negatively and positively respectively. Keywords: Real Exchange Rate, System GMM, Macroeconomics Factors JEL: E52, E62, C33, C53